2012
DOI: 10.1302/0301-620x.94b7.26943
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to long-term results of revision total knee replacement using press-fit intramedullary stems with cemented femoral and tibial components

Abstract: This was a retrospective analysis of the medium-to long-term results of 46 TC3 Sigma revision total knee replacements using long uncemented stems in press-fit mode.Clinical and radiological analysis took place pre-operatively, at two years post-operatively, and at a mean follow-up of 8.5 years (4 to 12). The mean pre-operative International Knee Society (IKS) clinical score was 42 points (0 to 74), improving to 83.7 (52 to 100) by the final follow-up. The mean IKS score for function improved from 34.3 points (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Lee et al [ 32 ] reported a survival rate of 83% at 8 years in 79 revisions, and Peters et al [ 25 ] reported a rate of 80% at 80 months in 43 revisions. This study showed a survival rate of 80%, which was lower than in other studies [ 33 , 34 ] but similar to that reported by Conlisk et al [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…Lee et al [ 32 ] reported a survival rate of 83% at 8 years in 79 revisions, and Peters et al [ 25 ] reported a rate of 80% at 80 months in 43 revisions. This study showed a survival rate of 80%, which was lower than in other studies [ 33 , 34 ] but similar to that reported by Conlisk et al [ 30 ].…”
Section: Discussionsupporting
confidence: 87%
“…Indeed, stem fixation has been used for a long time in revision TKA with satisfactory results. However, some problems have been described such as pain at the tip of the stem 22 and difficulties in positioning the stem itself if the femoral and tibia canal were not straight, 9 10 11 even with off-set design, thus impairing the efficacy of the treatment. Moreover, in many cases, the metaphyseal region has still fairly good bone quality and it seems reasonable to use it to fix the implant and not to bypass it with a stem.…”
Section: Discussionmentioning
confidence: 99%
“…So far, fixation has been achieved with intramedullary stems either cemented or press fit, with satisfactory results, albeit a few problems have been reported such as pain at the tip of the stem and difficulties in finding a correct position of the stem itself if tibia and femoral canals are not straight, with the need of offset devices. 9 10 11 …”
Section: Introductionmentioning
confidence: 99%
“…The TC3 implant (Depuy Synthes) has been used for many years as both a primary and revision implant with good clinical results in short-term [13][14][15][16][17] and long-term [18] observation. Damage of the prosthesis at the level of stem -condyle junction is a rare phenomenon, but it is described in the literature and carries serious consequences for the patient [6].…”
Section: Discussionmentioning
confidence: 99%